UPAYA PEMERINTAH DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP NASABAH FINTECH (PEER TO PEER LENDING) - Meirina Dewi Pratiwi; Erniwati Erniwati (Justici, 2022)
Abstract The development of technological advances has changed everything, including the pandemic that hit the world from 2020. Advances in the digital world besides the payment method that was originally only with cash turned into cashless or e-money, shopping that was previously face-to-face between sellers and buyers can now be done online. . The government through Bank Indonesia and the Financial Services Authority as the agency authorized to regulate Financial Technology. In accordance with the category, has issued technical regulations in regulations related to financial technology. In its development, many fintechs have had problems, both legal fintech and illegal fintech because they are not in accordance with government regulations. Legal protection is a description of the workings of legal functions to realize legal goals, namely justice, expediency and legal certainty. Efforts to modernize the legal framework to provide a legal landscape started with many people thinking that this online loan was an easy and fast solution to get money. The development of the fintech industry is also attached to the negative stigma of the community, especially in the way of billing. launching the Fintech Innovation Hub as a development center and becoming a national one stop contact for Fintech. In addition, following up on the agreement with Kominfo, OJK has prepared a Certificate Authority (CA) in the financial services sector. CA as a certificate issuer for a digital signature of financial service actors, can guarantee that an electronic transaction that is digitally signed has been secured and has legal force.